Analysis of genetic linkage in the cowpea vigna unguiculata - O. B., Kehinde; G. O., Myers; I., Fawole (Universiti Putra Malaysia Press, 1997)
Genetic analysis of 12 loci conditioning morphological characteristics indicated several linkages in cowpea Vigna unguiculata (L.) Walp). Using both backcross and F2 joint segregation data, these 12 loci were assigned to five linkage groups. The loci Pg for nodal pigmentation, Pf for purple flower, Pc for smooth seed coat, Na for narrow eye, and Br for brown seed coat make up linkage group 1 with the probable order Pg-Na-BrP-cPf The Bpd locus for branching peduncle was linked to Bp for brown dry pod and Dhp for pod dehiscence with the probable order Bpd-Bp-Dhp. The third linkage group consisted of loci Crl for crinkled leaf and Pt for sessile leaf Hastate leaf shape, Ha, and septafoliolate leaf number, Spt, belong to the fourth and fifth linkage groups, respectively.